Yeast killer plasmid mutations affecting toxin secretion and activity and toxin immunity function. - Bussey, H (1982)
M double-stranded RNA (MdsRNA) plasmid mutants were obtained by mutagenesis and screening of a diploid killer culture partially heat cured of the plasmid, so that a high proportion of the cells could be expected to have only on M plasmid. Mutants with neutral (nonkiller [K-], immune [R+]) or suicide (killer [K+], sensitive [R-] phenotypes were examined. All mutants became K- R- sensitives on heat curing of the MdsRNA plasmid, and showed cytoplasmic inheritance by random spore analysis. In some cases, M plasmid mutations were indicated by altered mobility of the MdsRNA by agarose gel electrophoresis or by altered size of in vitro translation products from denatured dsRNA. Neutral mutants were of two types: nonsecretors of the toxin protein or secretors of an inactive toxin. Of three neutral nonsecretors examined, one (NLP-1), probably a nonsense mutation, made a smaller protoxin precursor in vitro and in vivo, and two made full-size protoxin molecules. The in vivo protoxin of 43,000 molecular weight was unstable in the wild type and kinetically showed a precursor-product relationship to the processed, secreted 11,000-molecular-weight toxin. In one nonsecretor (N1), the protoxin appeared more stable in a pulse-chase experiment, and could be altered in a recognition site required for protein processing.